Fiscal Decentralization and Inequality in Western and Eastern Indonesia - Kartika, Metasari; Hendarmin; Mahendra, Fiqih Yusril; Mailyn, Frisilia Dameria; Mateen , Abdul (EcceS: Economics, Social, and Development Studies, 2025)
Income inequality across regions in Indonesia remains persistently high despite a stable national economy and ongoing fiscal reforms. This study examines disparities between Western and Eastern Indonesia by analyzing the roles of fiscal decentralization, economic growth, and unemployment from 2010 to 2022. Using a fixed effects model on 34 provinces, the analysis captures regional and temporal variations that shape inequality dynamics. The findings show that fiscal decentralization reduced inequality in Eastern Indonesia during 2010–2016 and in Western Indonesia during 2017–2022. Economic growth significantly increased inequality in Western Indonesia during 2010–2016, while unemployment reduced inequality in the same region and period. However, these effects weaken when control variables and time segmentation are introduced, indicating sensitivity to institutional and structural contexts. The implications of these findings underscore the importance of formulating fiscal policies tailored to regional characteristics, thereby strengthening the relevance of the theory of fiscal federalism and the kuznets hypothesis for future research aimed at addressing inequality in other developing countries. Keywords: Fiscal Decentralization; Economic Growth; Unemployment; Income Inequality.